A study of human adjustment in Fort McMurray - Technical manual ... - Gartrell, J. W. (University of Alberta Library, 1979)
The following technical manual is intended to document the computer file which contains the results of the A.O.S.E.R.P. Study of Human Adjustment in Fort McMurray. This manual contains several sections which refer either to the accompanying computer output from that file, or to the technical aspects of creating scales and indices to be used in the draft final report. The data file contains coded responses for 430 interviews conducted by the Population Research Laboratory, University of Alberta. The data was collected during May and June of 1979, and will be more fully described in the final report for this project. The computer readable file has been edited for record completeness, out-of-bounds codes and consistency of response. This, however, constitutes only a preliminary edit. Appropriate caution should be exercised in using the data. From an initial 433 interviews, three were totally eliminated because of their incompleteness (two cases where respondents quit partway through the interview), or because ...